A look over education; adoption, the parents of the second opportunity (Journal of Parents and Teachers, 2012)
This is an article in which the author reflects about adoption and talks about her opinion on the subject highlighting that adopted children need to feel helped, understood and loved no matter what.
Keywords: education; adoption; parents; development.; opinion